The Day of the Week Effect and LQ45 Stock Return During and After COVID-19 - Sinaulan, Carey; Kasingku, Frisky (Manunggal Halim Jaya, 2025)
This study examines whether there is a difference in the stock returns of LQ-45 companies' shares listed on the Indonesia Stock Exchange during Covid-19 and after Covid-19. This study uses a causal descriptive research design with a quantitative research method. This study uses the Kruskal-Wallis statistical test to test the hypothesis. The study results show that during the COVID-19 period, there was no significant difference in the stock return of LQ-45 companies. The same thing happened in the post-COVID-19 period, which showed no significant difference in the stock return of LQ-45 companies. Furthermore, the day of the week did not impact the return of LQ-45 companies listed on the Indonesia Stock Exchange in either period. This research provides important insights for capital market stakeholders related to the dynamics of stock behavior during and after the COVID-19 pandemic.